Gender-specific preferences regarding urban green areas - Bąkowska-Waldmann, Edyta; Piniarski, Witold (Quaestiones Geographicae, 2023)
Development of urban green areas and awareness of their value among citizens and local authorities is rapidly growing. This trend is not only the result of the coronavirus pandemic, but also reflects a belief in the role of green areas in reducing the negative effects of climate change and supporting overall well-being. As a consequence, more and more local governments are promoting local policies focused on the development of urban green areas with the participation of citizens. Using data collected in Zielona Góra, Poland, this study explores the gender patterns and differences in use and preferences according to the development of urban green areas. The main goals of the study were (1) to evaluate the possible relationship between gender and preferred types of visited green areas and transport modes used to reach them and (2) to explore the differences in expectations regarding the spatial development of green areas among men and women. The result of the study shows that women more often than men visit green areas closer to their place of residence and more often indicate playgrounds and other forms of greenery of an aesthetic function as proposed green areas. Furthermore, there are also differences regarding the means of transport used and preferable distance to green areas. Women visibly prefer green areas within the city centre, mostly use individual means of transport, and are more likely to travel on foot than men. Men prefer more distant green areas and mostly travel longer distances.